Effect of Biological and Environmental Factors on Legionella Growth in the Water Distribution Networks of Hospitals - Yahya Ehteshaminia; Hamid Mohammadi; Behzad Javadian (Mazandaran University of Medical Sciences, 2020)
Introduction and purpose: Legionella is a Gram-negative bacterium that is present worldwide in natural and man-made water sources, such as hospital water distribution networks. This bacterium causes two types of Legionnaires and Pontiac fever. This study aimed to review the effect of biological and environmental factors on legionella growth in the water distribution networks of hospitals. Methods: The databases of PubMed, Scopus, SID, Magiran, Web of Science, IranDoc, and google scholar were searched in this study, and the related articles were reviewed from 2001 to 2020.   Results: The symbiosis of Legionella with other bacteria in the biofilm and the presence of amoebae increase the Legionella growth in the water distribution networks of hospitals. For each increase in iron and manganese concentration, the chance of Legionella presence increases 1.22 and 3.3 times, respectively. Moreover, an increase in the concentration of zinc by 1 mg/L increases the density of Legionella by 17%. Furthermore, the concentrations of zinc greater than 200 g/L and less than 100 g/L are considered inhibitory. Following that, an increase in the concentration of copper by 1 mg/L reduces the density of Legionella by 7%. The temperature for growing Legionella is from 29°C to 40°C with an optimum temperature of 35°C. Conclusion: Amoebae, biofilm structure, metal ions, temperature, and pH affect the persistence and growth of Legionella. Sufficient knowledge of these factors can be useful in future studies to better design and construct hospital water distribution networks to provide a suitable solution to control this beneficial bacterium.